Pliozäne Verebnungen und Flussläufe in den schweizerischen Zentralalpen - Staub, Walter (ERDKUNDE, 1957)
The Grimsel-St. Gotthard area of the Swiss Alps is for a number of reasons particularly rewarding for geomorphological studies: the strata mostly dip steeply or are even vertical; terraces and levels which cut across the strata can therefore be interpreted as valley floor remains of the time of valley deepening. Furthermore the central Alps are a part of the Swiss Alps which was uplifted very early. The recognizable denudation features thus lead back to the period after the last, pronounced phase of folding before the Pontien. The peneplain of the Pontic period is very likely represented by the Gipfelflur (peak level). The valleys of the Tessin area exhibit step formation both longitudinally and transversally; according to H. Lautensach three stages in the deepening of the rivers can be proved: the lowest level (1,100 m.) is called the Sobrio-level, a medium (2,000— 1,800 m.) the Bedretto-level, and a high (2,100—2,000 m.) the Pettaneato-level. The Bedretto level in particular forms an almost uninterrupted sequence of terraces with summer pastures above the limit of forest. At Airolo these terraces turn southward with the Tessin valley. Consequently the Tessin river must at the time of their formation already have penetrated from the south into the Alpine range. There are, however, remains of valleys at even higher altitudes. The river of the Val Bedretta for instance flowed at first via the Val Piora, Val Campo and Val Luzzone towards the Greina following the zone of the Mesozoic Bünden-shales. The Greina itself flowed in a high valley of 5% Km. length, decreasing in altitude towards the North East from 2,350—2,194 m. At an altitude of 2,200 m. are also situated the remains of terraces which, beginning at the Furka Pass, extend on both sides of the Urseren valley and via the Oberalp Pass to the valley of the Vorderrhein. At this level of ± 2,200 m. — if the lowering effect of the Pleistocene glaciation is taken into account — lie several important passes, such as the Grimsel (2,164 m.), the St. Gotthard (2,100 m.) and the Oberalp Pass (2,044 m.). The most remarkable phenomena of this earliest valley formation are its width of 3—5 Km., the small gradient, and the fact that it continues into the tributary valleys at the same level. The ruggedness of the relief must have been very small at the time. The time of origin the author considers to have been the quiet period of the Plaisancien when, at the southern edge of the Alps, the Adriatic sea still penetrated into bays of the mountains. Together with the uplift during the following Astien (Upper Pliocene) commenced the deepening of the side valleys, a process which continued until the close of the great interglacial period. Another result of this investigation is that it was possible to establish a connexion between a cross-fold and the origin of the col on the St. Gotthard, as well as the Aare valley in the Grimsel area.